Licorice–wolfberry-derived nanomaterial improves the germination rate of wheat under salt stress by maintaining reactive oxygen species homeostasis - Wang, Wenya; Lian, Xiaomeng; Li, Zhiqian; Bao, Linfeng; Liu, Jiahao; Mao, Tingyong; Wang, Desheng; Yang, Lili; Ma, Long; Han, Lu (Frontiers in Plant Science, 2025)
IntroductionThe research on improving the salt tolerance of crops through plant nanobiotechnology has been extensively reported. However, the mechanism by which plant - derived nanomaterials enhance the germination rate of wheat under salt stress remains elusive. Unveiling the mechanism by which plant - derived nanomaterials boost the salt tolerance of wheat is conducive to safeguarding food security.MethodsHerein, we used mesoporous self-assembly licorice and wolfberry-derived complex nanomaterial (LW-CNs) to soak wheat (Triticum aestivum L) seeds.ResultsThe size and zeta potential of LW-CNs were 42.2±8.2 nm and -19.6±1.5 eV, respectively. After 4 days of salt stress, LW-CNs-soaked wheat seeds presented a higher germination rate (78.4±8.3 vs 54.4±8.5%) and protein content (44.0±0.1 vs 39.1±0.2 mg g-1), but no significant effect was observed on fresh weight (2.6±0.4 vs 2.3±0.4 g). LW-CNs significantly increased the pigment content (chlorophyll a: 0.11±0.0 vs 0.03±0.0 mg g-1, chlorophyll b: 0.05±0.0 vs 0.02±0.0 mg g-1, and carotenoids: 10.3±0.0 vs 2.9±0.0 μg g-1). LW-CNs alleviated salt-induced reactive oxygen species (ROS) accumulated through increase superoxide dismutase (917.4±8.7 vs 767.5±1.6 U g-1), peroxidase (2458.7±5.0 vs 2070.5±14.8 U g-1), and catalase (158.3±3.9 vs 112.0±3.2 μmol min-1 g-1) activity. Soaking in LW-CNs maintained ROS homeostasis also through the ascorbic acid–glutathione cycle. Furthermore, LW-CNs elevated the K⁺/Na⁺ ratio within wheat seeds and augmented the activities of nitrogen metabolism enzymes.ConclusionOverall, our study demonstrates that soaking seeds with plant - derived nanomaterials promotes the growth and nutrient absorption of wheat under salt stress by modulating the homeostasis of reactive oxygen species (ROS) and the K⁺/Na⁺ ratio/.